Technology Adoption for Bhuddist Temple Management - Chiralaksanakul, Anukal (NIDA Business Journal, 2024)
This study investigates the technology adoption for Bhuddist temple management. Usage adoption of technology should increase the efficiency of temple as in other non-profit organizations, and help reduce the gap between the temple and Bhuddists. The study employs qualitative in-depth interviewing method to investigate (1) the scope of technology used in the operations of the temples, (2) the future development of technology used to improve the temple’s efficiency and Bhuddists access, and (3) key success factors and obstacles in technology adoptions. The interviews are conducted with three monks who are directly in charge of technology management of their own temple. The duration that these three monks work in their role is averaged at fifteen years. The results can be summarized as follows. There are three aspects that the temple brings technology into usage: Bhuddism propagation, Bhuddist ceremony broadcasting, and temple administration support. The main use is in Bhuddism propagation aspect. Temples have not paid much attention in using the technology to increase their efficiency and to reduce the gap between their temple and Bhuddists. Future technology development focuses on database development for keeping temple data and on multimedia system for broadcasting of temple Bhuddist activities and ceremonies. Another important future goal is to promote the Bhuddist way of lives through technology, i.e., to help Bhuddist maintain the Five precepts, promote meditation and inner wisdom (introspection) through technology. An important key success factor in the usage adoption is organizational; namely, the far-sighted vision of the abbot or governing monks, the availability of monks competent in technology, and the sufficient temple budget. Social factors that influence the technology adoption is the behavioral change of Bhuddists who tends to employ digital technology extensively in their daily lives.